2015
DOI: 10.1021/acs.orglett.5b00067
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Heterocyclization of O-Propargylated Aromatic Hydroxyaldehydes as an Expedient Route to Substituted Chromenopyridines under Metal-Free Conditions

Abstract: A concise and regioselective approach to the synthesis of chromenopyridine and chromenopyridinone derivatives was developed. The synthetic strategy relies on the O-propargylation of aromatic hydroxyaldehydes followed by reaction with propargylamine. The intramolecular cycloaddition reaction between the alkyne and azadiene, which is formed as an intermediate, furnished the desired skeletons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 56 publications
1
43
0
Order By: Relevance
“…Keskin et al . developed a brief, high yielding and regioselective approach for the synthesis of pyridocoumarin derivatives 295 using intramolecular cycloaddition reaction between the alkyne and azadiene groups of 292 , which is formed as an intermediate from aromatic hydroxyaldehydes 264 , propargyl bromide 288 and propargyl amine 290 and followed by oxidation with chromic acid (Scheme ).…”
Section: Synthesis Of Pyridocoumarinsmentioning
confidence: 99%
“…Keskin et al . developed a brief, high yielding and regioselective approach for the synthesis of pyridocoumarin derivatives 295 using intramolecular cycloaddition reaction between the alkyne and azadiene groups of 292 , which is formed as an intermediate from aromatic hydroxyaldehydes 264 , propargyl bromide 288 and propargyl amine 290 and followed by oxidation with chromic acid (Scheme ).…”
Section: Synthesis Of Pyridocoumarinsmentioning
confidence: 99%
“…Pale brown viscous oil (0.30 g, 68 %). (ddd, J 8,7 = 8.1,J 8,9 = 7.1,J 8,10 = 1.4 Hz,1 H,3 H,arom),2 H,arom), 2.35 (s, 3 H, 1′-H) ppm. s,2 H,8.17 (dd,J = 7.9 and 1.5 Hz,2 H,arom),7.91 (dd,J 6,5 = 7.7,J 6,4 = 1.3 Hz,1 H,7.70 (d,J = 7.7 Hz,2 H,arom),1 H,arom),3 H,arom),7.30 (t,J = 7.6 Hz,1 H,4.35 (s,4 H, ppm.…”
Section: -{Bis[3-(3-nitrophenyl)prop-2-ynyl]amino}benzaldehyde (28)mentioning
confidence: 99%
“…[5] Pierre et al reported that naphthyridine derivative 6 inhibits protein kinase CK2, which is relevant for the treatment of cancer [6] (Figure 2). [8] Chromenopyridine scaffold 9 was obtained in just two steps, and the key reaction was an alkyne cyclization [9] which took place without metals to promote the process. [7] Most of the procedures involve many steps and require complicated starting materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…And the hydroxy group provided a handle for the generation of ethers (7 a and 8 a) through reaction with a bromo-containing molecule. [14] Significantly, participation of both aldehyde and hydroxy groups enabled the synthesis of another ring structure on the original naphthalene framework (9 a). [15] In summary, we have proposed an enaminone-directed CÀ H functionalization method and demonstrated its utility in the Rh III -catalyzed synthesis of naphthalenes, through coupling with either alkynes or a-diazo-b-ketoesters.…”
Section: Angewandte Chemiementioning
confidence: 99%